Barriers to stopping neuroleptic (antipsychotic) treatment in people with schizophrenia, psychosis or bipolar disorder. (July 2020) - Moncrieff, Joanna; Gupta, Swapnil; Horowitz, Mark Abie
Most guidelines recommend long-term, indefinite neuroleptic (or antipsychotic) treatment for people with schizophrenia, recurrent psychosis or bipolar disorder, on the basis that these medications reduce the chance of relapse. However, neuroleptics have significant adverse effects, including sexual dysfunction, emotional blunting, metabolic disturbance and brain shrinkage, and patients often request to stop them. Evidence for the benefits of long-term treatment is also not as robust as generally thought. Short-term randomised trials show higher rates of relapse among those whose neuroleptic treatment is discontinued compared with those on maintenance treatment, but they are confounded by adverse effects associated with the withdrawal of established medication. Some longer-term studies show possible advantages of medication reduction and discontinuation in terms of improved social functioning and recovery. Therefore, there is a good rationale for supporting patients who wish to stop their medication, especially given the patient choice agenda favoured by The National Institute for Clinical Excellence (NICE). The major barrier to stopping antipsychotics is an understandable fear of relapse among patients, their families and clinicians. Institutional structures also prioritise short-term stability over possible long-term improvements. The risk of relapse may be mitigated by more gradual reduction of medication, but further research is needed on this. Psychosocial support for patients during the process of reducing medication may also be useful, particularly to enhance coping skills. Guidelines to summarise evidence on ways to reduce medication would be useful. Many patients want to try and stop neuroleptic medication for good reasons, and psychiatrists can help to make this a realistic option by supporting people to do it as safely as possible, with the best chance of a positive outcome.